PENGEMBANGAN MEDIA VIDEO ANIMASI PEMBELAJARAN BERBANTUAN CANVA PADA MATERI BANGUN DATAR KELAS 5 SD NEGERI 1 BATANGSAREN - Fajar Rasyid Armansyahrudin; Aditya Pringga Satria; Nugrananda Janattaka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop an animated learning video as an instructional media assisted by the Canva application on plane geometry material for fifth-grade students of SD Negeri 1 Batangsaren that is practical and effective for use in the learning process. The background of this study is based on the limited use of engaging and interactive learning media, which has an impact on students' low interest and understanding of mathematics material. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were fifth-grade students of SD Negeri 1 Batangsaren. The research instruments used included material expert validation questionnaires, media expert validation questionnaires, teacher response questionnaires, and student response questionnaires. The results showed that the validity of the developed Canva-assisted animated learning video media obtained a score of 92% from material experts and 89% from media experts. The teacher's response to the media reached 90%, while students' responses reached 88%. This study concludes that the Canva-assisted animated learning video media on the topic of area and perimeter of plane figures is valid and can be implemented as a learning medium to improve students' interest and understanding in mathematics learning at the elementary school level.